Motives of sadness and despair in the works of Yitzhak Rabinowitz - Rahima, Majeed (Al-Adab Journal, 2025)
This research includes an overview of the life of the Jewish writer and writer Yitzhak Rabinowitz and his bitter experience in life and society and its impact on his productions. He was born in Poland in 1884 to “wealthy parents.” We find that when his father’s financial condition worsened and his mother’s illness, who was naturally ill, increased, when he was thirty years old, he felt sadness and despair, which had already reached a dead end and he had no choice but to immigrate to America, to the place where his children had settled earlier. There is no doubt that sadness, in its simplest connotations, is an emotional state and an internal feeling in which despair, pain, depression, and a sense of frustration are mixed. It is one of the most important phenomena that was frequently mentioned in modern Hebrew poetry. It seems that the reasons for the sadness of the Jewish writer have many motives, including “the psychological motive that is represented by the inability of the Jewish individual to integrate with his surroundings,” including the “social motive that manifests itself in class disparity and cases of poverty,” and among them a political motive that “manifests itself in the social system.” The authorities and their oppressive practices towards the Jewish individual and force him to emigrate from his country of origin. Hence, I was motivated to choose this topic as a field for research and study, taking the Jewish poet (Yitzhak Rabinowitz) as a model representing this phenomenon, through extrapolation of his poetic productions, extracting from them poetic texts that were dominated by the tendency of sadness and despair, and trying to identify the causes and motivations. Which affected his psychological world, and made him a sad and desperate writer who sheds his tears and vents his sadness and pain. The importance of the research comes from the importance of the phenomenon that it seeks to address, as well as from the importance of the poems that it chooses for study. The phenomenon of sadness - which has a striking presence in the poetry of (Yitzhak Rabinowitz) - stops the student and raises many questions about the prevalence of this phenomenon and its control over his psychological world. For reference, most Jewish poets suffer from estrangement, as a result of their distance from the homelands in which they lived due to social and political unrest, or as lovers overflowing with affection and longing for loved ones who have departed and others who have left. The writer Yitzhak Rabinowitz embodied the tragedy of sadness in his poetry, and his psychological pessimism reached its peak. Thus, the researcher devoted himself to studying (the motives of sadness and despair in the works of Yitzhak Rabinowitz), complementing the efforts of the distinguished professors and researchers who preceded him, in accordance with the analytical method that came in an introduction, three chapters, and a conclusion. The research reached an important result, which is the prevalence of this type of sad poetry in Modern Hebrew poetry is a reflection of the historical and cultural context, and the literary styles used by Hebrew poets to express their feelings and thoughts.